The relationship between leadership styles and job satisfaction: a case study in public sector organizations in Kota Kinabalu, Sabah / Nurfarahain Shahzana Kesmat Ekbal and Nor Syazwanie Mohd Shafuwan - Kesmat Ekbal, Nurfarahain Shahzana; Mohd Shafuwan, Nor Syazwanie (2016)
One of the most critical success factors in any organization, whether public or private, is its workforce. An organization cannot succeed without their personnel's efforts and commitment. Therefore, an organization needs effective leaders and employees to achieve their objectives. Leadership has a strong effect on the attitude of employees towards their jobs. The role of leaders in today's organizations has changed and the success of any organization relies on the leadership styles practiced by the leaders. In fact, organisational success depends upon effective leadership and job satisfaction. A capable leader is the one that provides direction to the organisation and let the followers achieve their goals. According to Mintzberg (2010) true leaders engage others with their consideration and modesty because they involve themselves in what they are actually doing not for individual gains. A review of the available literature indicates that there is a wide variety of different theoretical approaches to explain leadership process (Northouse, 2010). However, the transformational and transactional leadership framework has received considerable research support (Bass & Avolio, 1993). Job satisfaction refers to how content an individual is with his or her job in an organization. It has been used as a mean to allure and retain the qualified and performance employees in the organization (W.A. Wan Omar & Fauzi Hussin, 2013). Employee's psychological and physical well-being (llardi, Leone, Kansser, & Ryan, 1983) is enhanced by high job satisfaction which in turn affects employee's performance in a positive manner (Vroom, 1964; Porac, Ferris, & Fedor, 1983). Additionally, it has been concluded that leadership impacts job satisfaction and organisational commitment (Lok &Crawford, 1999, 2001; William & Hazer, 1986; Mosadegh Rad & Yarmohammadian, 2006)